A Novel Quantitative Method for Evaluating Surgical Outcomes in Craniosynostosis: Pilot Analysis for Metopic Synostosis. Issue 1 (March 2014) - Weathers, William M.; Khechoyan, David; Wolfswinkel, Erik M.; Mohan, Kriti; Nagy, Andrew; Bollo, Robert J.; Buchanan, Edward P.; Hollier, Larry H.
Objective assessment of head shape has been an elusive goal in the management of craniosynostosis patients. Clinical judgment, craniometric indices, and computed tomography scans are the primary means through which a surgeon assesses this patient population. The purpose of this study was to examine and discuss the utility of the STARscanner for evaluation of surgical outcomes in metopic synostosis patients. A retrospective chart review of patients with metopic synostosis who underwent fronto-orbital advancement with pre- and postoperative STARscanner imaging at Texas Children's Hospital was performed. Two patients were identified and evaluation and discussion of the data produced by the STARscanner was undertaken. A novel symmetry index created by the authors, called the anterior–posterior volume ratio (APVR), was discussed for use in metopic synostosis patients. The postoperative growth metrics demonstrated an interval increase compared with the preoperative data. The anterior symmetry ratio, posterior symmetry ratio, overall symmetry ratio, cranial vault volumes, cranial vault asymmetry index, and cephalic ratio were not found to be useful in evaluating resolution of dysmorphology after fronto-orbital advancement in metopic synostosis. The APVR does not characterize dysmorphology, but may help show degree of expansion of the anterior cranial vault after fronto-orbital advancement. The STARscanner imaging device does not appear to have significant utility in characterizing head shape for surgical outcomes assessment in metopic synostosis. The minor utility of this device may be that it is a safe and fast way to derive growth parameters for both short-term and long-term follow-up of cranial vault remodeling.